In Search of Libra for Memory - Kareniauskaitė, Monika (Lietuvos istorijos studijos, 2017)
About the thesis of Mingailė Jurkutė “Memory of the Lithuanian guerilla war: soviet, non-soviet and diaspora’s narratives”